PENGARUH ATRIBUT PRODUK TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN SMARTPHONE MEREK ASUS DI KOTA PALU - SARI, PURNA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
The purpose of this research is to know 1) the effect of product attribute variable consisting of product quality, features and design simultaneously to customer satisfaction using Asus brand smartphone in Palu City. 2) the effect of product quality variable on consumer satisfaction using Asus brand smartphone in Palu City. 3) the influence of feature variables on consumer satisfaction using Asus brand smartphone in Palu City. 4) the influence of design variables on consumer satisfaction using Asus brand smartphone in Palu City. This type of research is a survey research. The sample size is 60 respondents by using snowball sampling technique. The method of analysis is statistical analysis of Multiple Linear Regression. Result of research 1) variable of product attribute consisting of product quality, feature and design simultaneously have significant effect to consumer satisfaction using Asus brand smartphone in Palu City. 2) variable of product quality significantly influence to consumer satisfaction using Asus brand smartphone in Palu City. 3) feature variable significantly influence consumer satisfaction using Asus brand smartphone in Palu City. 4) design variables significantly influence consumer satisfaction using Asus brand smartphone in Palu City.